The Literary Myth of Ukraine in the Works of the Diaspora Authors, 1920s to 1950s - Olha Slonovska (Vasyl Stefanyk Precarpathian National University, 2019)
Ukrainian literature in emigration is part of the Ukrainian cultural heritage. Its analysis shows that, unlike Soviet Ukrainian literature, it enhanced the importance of the national idea proclaimed by T. Shevchenko. The diaspora literature of the 1920s-1950s created the mythological paradigm of the occupied nation that was superior to the invader, a 'source code' for a future Ukraine in its own ancestral land in the centre of Europe, not for Ukraine in exile as it was viewed by Ukrainian politicians in emigration. The literary myth of Ukraine established by the diaspora authors is a vitaistic and consolidating metaphysical phenomenon that even now has a powerful impact on national consciousness.